THE FINANCING FOR DEVELOPMENT NEGOTIATIONS AT THE UNITED NATIONS: AN ASSESSMENT OF ITS HISTORY, DRIVERS AND THE PERSPECTIVES FOR BRAZIL’S ENGAGEMENT - Lucas Pavan Lopes (Revista Tempo do Mundo, 2022)
Since the adoption of the 2030 Agenda for Sustainable Development and the Addis Ababa Action Agenda (AAAA), in 2015, the financing for development negotiations at the United Nations (UN) have witnessed growing tendencies towards fragmentation and challenges for developing countries in the negotiation front. This article intends to analyze the current state of negotiations and reflect upon the perspectives that are open for Brazilian involvement. Starting with an historical description of the multilateral process, from its inception in the 1960s, with the formulation and upholding of the concept of official development assistance (ODA), to the birth of the current conceptual framework, after the Monterrey Consensus, in 2002, the text will walk through the major innovations of the AAAA. It will also explore the current major tendencies, with mentions to the challenges of financing a universal and diversified agenda, the causes of the so-called prolonged crisis of ODA and the difficulties in achieving consensus in the negotiations. Through a reflection upon Brazilian current status, at the same time a member of the Group of 77 and China (G77 + China) and a candidate for accession to the Organisation for Economic Co-operation and Development (OECD), we will assess the fields in which dissents remain and in which convergence is taking place, including international cooperation in tax matters, development cooperation and private sector involvement in financing for development.